Legal Measures Applicable to Public Service Concessions - Tuntimas, Anukool; Sutthibodee, Suksamai; Yimwilai, Chaiya (Ph.D. in Social Sciences Journal, 2022)
This research article aims to study to (1) the concepts, theories in the contract of public service concession between the government and private. (2) the problems and conditions regarding the granting of public service concessions to private sectors in Thailand. (3) the legal measures regarding the granting of public service concessions to foreign private entities. (4) To improve the legal measures for providing public service concession services to private individuals in Thailand. The researchers used the qualitative research methodology by using 2 methods of data collection, namely documentary research and in-depth interviews and analyzed the data by using content analysis techniques and comparison interpretation. The result of the research shows that the public service concession agreement should consider the draft of the contract which is an integral part of TOR since the bidding for the project. To make it transparent and is clear in the implementation of the contract and creating a mutual understanding of the content and objectives of the work between the parties. Including specifications Including specifying the scope of work and standards clearly. To reduce problems in breach of contract. In addition, the draft check before signing the contract for public service. By the Office of the Attorney General should specify a person who has expertise and suitable for drafting the contract and requiring both parties to call to inform the parties of the details of the contract and should consider only the legal conditions in the contract only should not include financial details and benefits in the contract and when the contract has a dispute in arbitration, the result should be final.